Practice of treating Chronic Subdural Hematoma (cSDH) among Neurosurgeons in Nepal: A nationwide survey with literature review - Sedain, Gopal; Pradhanang, Amit; Rajbhandari, Binod; Sharma, Mohan Raj (Nepal Journal of Neuroscience, 2023)
Objectives: To survey Nepali neurosurgeons regarding the practice of managing chronic subdural hematomas (cSDH). Methods and Materials: A survey questionnaire was sent to all neurosurgeons practicing in Nepal from the database of the Nepalese Society of Neurosurgeons (NESON). Results: 60% (50/84) responded to the questionnaire. There was variation in practice among neurosurgeons regarding the use of drain and the administration of antiepileptics. However, many concurred regarding postoperative computed tomography scan, size of the burr hole, and positioning after surgery. Conclusion: For a common neurosurgical procedure like drainage of cSDH, scientific evidence keeps on changing. Based on the available evidence we need to change our practice for the best possible outcomes. For most of the variables studied, there is concordance with available scientific evidence among neurosurgeons regarding cSDH management in Nepal.